Two new members of the family Niphargidae (Gammaridea) from Spain (Contribution to the Knowledge of the Amphipoda 281) - Karaman, Gordan S. (Biologia Serbica, 2016)
Two new members of the genus Niphargus Schiödte, 1849 (Amphipoda, fam. Niphargidae) from the subterranean waters of Spain are described and figured: Niphargus notenboomius sp. n. from wells near Angles (province Gerona) and Niphargus laisi geronensis ssp. n. from wells near Garriguella (prov. Gerona). Both taxa are also cited for some other localities of Spain. Taxonomical relations of these two taxa with respect to other members of the genus Niphargus from Western Europe are discussed.